Post-traumatic stress, anxiety and depression following miscarriage or ectopic pregnancy: a prospective cohort study. Issue 11 (2nd November 2016) - Farren, Jessica; Jalmbrant, Maria; Ameye, Lieveke; Joash, Karen; Mitchell-Jones, Nicola; Tapp, Sophie; Timmerman, Dirk; Bourne, Tom
Abstract : Objectives: This is a pilot study to investigate the type and severity of emotional distress in women after early pregnancy loss (EPL), compared with a control group with ongoing pregnancies. The secondary aim was to assess whether miscarriage or ectopic pregnancy impacted differently on the type and severity of psychological morbidity. Design: This was a prospective survey study. Consecutive women were recruited between January 2012 and July 2013. We emailed women a link to a survey 1, 3 and 9 months after a diagnosis of EPL, and 1 month after the diagnosis of a viable ongoing pregnancy. Setting: The Early Pregnancy Assessment Unit (EPAU) of a central London teaching hospital. Participants: We recruited 186 women. 128 had a diagnosis of EPL, and 58 of ongoing pregnancies. 11 withdrew consent, and 11 provided an illegible or invalid email address. Main outcome measures: Post-traumatic stress disorder (PTSD) was measured using the Post-traumatic Diagnostic Scale (PDS), and anxiety and depression using the Hospital Anxiety and Depression Scale (HADS). Results: Response rates were 69/114 at 1 month and 44/68 at 3 months in the EPL group, and 20/50 in controls. Psychological morbidity was higher in the EPL group with 28% meeting the criteria for probable PTSD, 32% for anxiety and 16% for depression at 1 month and 38%, 20% and 5%, respectively, at 3 months. In the control group, no women met criteria for PTSD and 10% met criteria for anxiety and depression. There was little difference in type or severity of distress following ectopic pregnancy or miscarriage. Conclusions: We have shown a large number of women having experienced a miscarriage or ectopic pregnancy fulfil the diagnostic criteria for probable PTSD. Many suffer from moderate-to-severe anxiety, and a lesser number depression. Psychological morbidity, and in particular PTSD symptoms, persists at least 3 months following pregnancy loss.